PRAKERIN Monitoring Web-Based Information System with QR Code Implementation at SMK Negeri 3 Kolaka - Ariani, Irma; Adawiyah, Rabiah; Sagala, La Ode Hasnuddin S; Zainuddin, Noorhasanah; Pradipta, Anjar; Pasrun, Yuwanda Purnamasari (Media of Computer Science, 2025)
Student attendance monitoring during industrial internship programs (Prakerin) is still commonly carried out manually, leading to potential data inaccuracy, reporting delays, and inefficiency in school administration. The issue becomes more complex when a large number of students are placed in different locations, making it difficult for supervising teachers to monitor attendance in real time. This study aims to design and develop the PRAKERIN Monitoring Web-Based Information System with QR Code Implementation at SMK Negeri 3 Kolaka. The system was developed using the Waterfall model, which consists of requirement analysis, system design, implementation, and testing. Black-box testing confirmed that all system functions operated validly as intended. External evaluation using a Likert-scale questionnaire with 15 respondents indicated an average satisfaction rate of 82%, with 78% agreeing that the interface facilitated attendance access, 80% stating that the system improved real-time tracking, and 86% confirming that automated reporting supported evaluation. The findings demonstrate that the system is feasible, effective, and capable of enhancing transparency, accuracy, and efficiency in Prakerin monitoring.